Enhancement of flexural modulus and strength of epoxy nanocomposites with the inclusion of functionalized GNPs using Tween 80 - Wan Zateel Aqmaer Wan Ab Halim; Ramli Junid; Norazliane Sazali; Januar Parlaungan Siregar; Jeefferie Abd Razak; Deni Fajar Fitriyana; Tezara Cionita; Jamiluddin Jaafar (Journal of Engineering and Applied Science, 2024)
Abstract In this work, epoxy nanocomposite was prepared with the inclusion of unfunctionalized as-received GNPs (ARGNPs) and functionalized GNPs using surfactant Tween 80 (T80GNPs) in the epoxy resin using a mechanical stirrer. ARGNPs were used as it is, while T80GNPs were prepared through the adsorption of surfactant onto GNPs’ surface using a sonication procedure in an ultrasonic bath. Characterization of nanoparticles using SEM shows that ARGNPs indicated a softer image representing a thinner layer of graphene stacks compared to T80GNP which has a tangible solid-looking image resulting from the sedimentation during the process of filtration. Elementally, both ARGNPs and T80GNPs were found to contain carbon, oxygen, and sulfur, as indicated by the EDX spectrum, with the C/O ratio for T80GNPs being 34.7% higher than that for ARGNPs, suggesting the adsorption of Tween 80 molecules on the GNPs after functionalization. FTIR spectroscopy confirms the attachment of Tween 80 molecules on GNPs surface with T80GNPs spectrum indicated higher peak intensity than ARGNPs. Flexural testing demonstrated that the addition of 0.9 wt.% ARGNPs and 0.9 wt.% T80GNPs to the epoxy increased the modulus of the nanocomposites to 72.1% and 82.6%, respectively, relative to neat epoxy. With the same amount of particle content, both nanocomposites showed increased strength, with ARGNPs and T80GNPs exhibiting strengths of 70.5% and 87.8%, respectively, relative to neat epoxy.